Case report: Revealing the rare—a Brody Disease patient from Turkey expanding the phenotype - Şahin, Ayça; Badakal, Esmer Zeynep Duru; Kovancılar Koç, Müge; Uysal, Hilmi; Başak, Ayşe Nazlı (Frontiers in Genetics, 2023)
Brody Disease is an exceptionally rare, autosomal recessive myopathy attributed to the pathogenic variants in the ATP2A1, which encodes the sarcoplasmic/endoplasmic reticulum Ca (2+) ATPase type 1 protein SERCA1. It was first described by Brody IA in 1969. To date, only thirty-three Brody families with forty-seven patients have been reported in the literature, and the disease prevalence is considered as 1 in 10 million, demonstrating the peculiarity of the disease. Clinical characteristics of Brody Disease include muscle stiffness after exercise, myalgia, and muscle cramps. Brody Disease patients generally have disease onset in the first decade, and genetic diagnosis is delayed as a consequence of both the rareness and the mild course of the disease. Here, we report a Turkish Brody Disease patient with a homozygous c.428G>A p.Arg143Gln (NM_004320.4) missense mutation in the ATP2A1. The male patient, whose symptoms started at the age of 14–15, is now 36 years old. His clinical manifestations are athletic appearance, exotropia, slightly elevated creatine kinase (CK), mild progressive proximal muscle weakness in the lower extremities, muscle cramps, pain and stiffness. The patient described here has a very mild progression with an onset in the second decade, expanding the Brody Disease phenotype. The study also implies that in the era of emerging genetic therapies, the routine testing of patients with myopathies is a prerequisite since not only future therapies will be designed on molecular findings, but also currently available symptomatic and palliative treatment options will be more precisely applied.